(untitled) (Global Journals of Research in Engineering, 2011)
The present paper is completely devoted on derivation of some basic fundamental relations in generalized thermodiffusive micropolar elasticity with fractional-ordered derivatives. The generalized heat conduction and mass diffusion equations have been modified by using fractional calculus. A variational principle is obtained and hence the uniqueness theorem for those equations has been proved.